2016
DOI: 10.1074/jbc.m115.709626
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Palmitate Supply Impairs Intestinal Insulin Signaling via Ceramide Production

Abstract: The worldwide prevalence of metabolic diseases is increasing, and there are global recommendations to limit consumption of certain nutrients, especially saturated lipids. Insulin resistance, a common trait occurring in obesity and type 2 diabetes, is associated with intestinal lipoprotein overproduction. However, the mechanisms by which the intestine develops insulin resistance in response to lipid overload remain unknown. Here, we show that insulin inhibits triglyceride secretion and intestinal microsomal tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 54 publications
1
25
0
3
Order By: Relevance
“…It was suggested that a mechanism that can differentiate between the metabolic effect of MUFA and saturated fatty acids is related to the palmitic acid‐ceramide pathway. This pathway accounts for impaired intestinal insulin sensitivity, which occurs within several hours following initial lipid exposure . However, this can apply to short‐term supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that a mechanism that can differentiate between the metabolic effect of MUFA and saturated fatty acids is related to the palmitic acid‐ceramide pathway. This pathway accounts for impaired intestinal insulin sensitivity, which occurs within several hours following initial lipid exposure . However, this can apply to short‐term supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate triglyceride deposition into cytoplasmic lipid droplets enlarges the intracellular pool of fatty acyl-CoA thereby providing substrate for oxidative and non-oxidative (e.g. ceramide synthesis [10, 11]) metabolic pathways leading to oxidative stress, cellular dysfunction and apoptosis and insulin resistance [43]. However, such packaging of lipid excess into lipid droplets can also be regarded as an adaptive response of the tissue to accommodate an excessive energy supply while keeping low concentrations of lipotoxic intermediates [44].…”
Section: Discussionmentioning
confidence: 99%
“…The ectopic presence of triglycerides and lipid metabolites such as ceramides has been related to lipotoxicity and cardiomyocyte apoptosis [9]. Interestingly, a palmitic acid-ceramide pathway accounts for impaired insulin sensitivity [10], whereas ceramide inhibition has been suggested to be an effective deterrent to heart disease risk in conditions like hyperinsulinemia [11]. In fact, a positive correlation between cardiac lipid accumulation and cardiac dysfunction has been established giving rise to the term lipotoxic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…54 Ceramides are found in large quantities in cell membranes and contribute to cellular signaling mechanisms, particularly cell death, partially reproducing the effect of palmitic acid on insulin signaling. 55 Triacylglycerols and diacylglycerols are usually thought of as energy metabolites, although they can also be signaling molecules and have long been implicated in the occurrence of metabolic syndrome. 56…”
Section: The Fecal Metabolome and Lipidomementioning
confidence: 99%